Framework for developing reverse mortgage market in Malaysia - Mohammed, Mohammed Ishaq (2018)
Malaysia is expected to become an ageing nation by the year 2020 when the population of the elderly people aged 60 years and above will hit the 10 percent globally recognised benchmark of ageing nation. Despite the fact that the elderly population are recognised as asset-rich, they are however considered to be cash-poor, thus becoming vulnerable to the risk of financial insecurity. In an attempt to trigger discussion into the possibility of providing elderly compliant financial product that can be used to address old-age financial needs, this research aimed at developing a framework for reverse mortgage market development in Malaysia. The research used convergent-parallel mixed-method research design in a qual-QUAN context to administer interviews and survey questionnaires to bank professionals and household heads in Johor state respectively. Using a critical case sampling strategy, a total of 9 bank professionals were purposefully selected from eight commercial banks and Bank Negara Malaysia to participate in the interview. In the quantitative strand, a multi-stage purposeful random sampling strategy was used to administer questionnaires to a total of 600 household heads/representatives in Batu Pahat District. A total of 223 questionnaires were finally used in the analysis. The qualitative data was coded, categorised and then later analysed using Computer-Aided Qualitative Data Analysis Software (CAQDAS) Nvivo version 10. The quantitative data was analysed using Statistical Package for Social Science (SPSS) and Partial Least Squares Structural Equation Modelling Software, SmartPLS 3.2.6. The findings revealed that various economic, socio-demographic, institutional/political and behavioural factors would exert varying degree of influence in the development of reverse mortgage market in Malaysia. Similarly, the findings suggest that although individuals showed high willingness to use reverse mortgage in the future, the financial institutions may be sceptical to provide the product unless there is strong commitment from the government.